KEDUDUKAN HARTA BERSAMA AKIBAT PERCERAIAN MENURUT UNDANG – UNDANG NO 1 TAHUN 1974 TENTANG PERKAWINAN - I Wayan Artana (Kerta Dyatmika, 2019)
ABSTRACT Divorce is a much discussed issue in public, long before the existence of Law No. 1/1974. That matter has become a conversation, partly because in reality in society a marriage ends up in a divorce, and this seems to happen easily. Even sometimes there are many divorces because of arbitrary acts committed by men. Conversely, it is not easy as a husband can do to his wife in the case of a wife feeling compelled to divorce with her husband, so it often happens that a wife still has the status of a wife but in reality no longer feels herself as a wife.Based on the background above is: 1) What is the status of community property in a marriage due to divorce?; 2) How can separating the community property be carried out due to Divorce?The method used in this study is empirical juridical research. The type of data used is primary data obtained by collecting data from informants in the field (field research). Primary data is data obtained directly from the first source. While secondary data include official documents, books, journals in the form of reports and so forth. Data collection used library research by collecting written legal material in the form of laws, books. Data processing and analysis techniques are data collection processes that are based on all data that has been processed and obtained from primary data in the form of legislation and secondary data taken from direct research. After the data obtained is collected, then it is then processed and analyzed in a quantitative and then presented in a descriptive analysis.The conclusion can be drawn is that all own property together obtained during a marriage is a community property. When a marriage ends due to divorce, all own property together obtained during the marriage (gono-gini assets) must be separated equally in a part for the ex-husband and a part for the ex-wife. The authorities can be asked for help if there are difficulties in the separating of assets. Keywords: community property, divorce, Law No.1/1974